Ketahanan Sepuluh Genotipe Kedelai terhadap Penyakit Karat - Sumartini Sumartini; Apri Sulistyo (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2016)
Rust disease caused by Phakopsora pachyrhizi can reduce soybean yields up to 75%. One solution to overcome the rust disease is by planting resistant varieties. The aim of this study was to evaluate the resistance of 10 soybean genotypes to rust disease. The research was conducted in the greenhouse. The experiment was arranged in a randomized completely block design with three replications. Inoculation of rust pathogen on 3 weeks-old plants was done by spraying urediniospore suspension (density 104 mL-1) to the surface of the leaves on the 10 soybean genotypes (MLGG 0005, MLGG 0253, MLGG 0465, MLGG 0470, var. Argomulyo, var. Tanggamus, var. Wilis, var. Burangrang, var. Grobogan, dan var. Dering 1). The results showed that all soybean genotypes were classified as moderately resistant to rust diseases based on the method of IWGSR. Although the plants were infected by rust disease, var. Wilis and Dering 1 produced the highest seed yield per plant (7.15 and 5.21 g, respectively), due to the good appearance of the plants, and the high number of branches, reproductive nodes, and number of filled pods. Therefore, these genotypes might be used as a good germplasm accession.